Global behavior of the difference equation $x_{n+1}=frac{Ax_{n-1}} {B-Cx_{n}x_{n-2}}$ - R. Abo-Zeid; Cengiz Cinar (Boletim da Sociedade Paranaense de Matemática, 2013)
The aim of this work is to investigate the global stability, periodicnature, oscillation and the boundedness of all admissible solutions of the difference equationx_{n+1} =frac{Ax_{n−1}} {B − Cx_nx_{n−2}}, n = 0, 1, 2, . . .where A,B,C are positive real numbers.